CLINICAL AND LABORATORY FEATURES OF COVID 19 IN PEOPLE - Berdiyarova Shokhida Shukurullayevna; Eshnazarova Ruxshona Olimjon kizi; Xolmatova Sevinchoy Umid qizi; Muhammadiyeva Muxlisabonu Zokir qizi (Web of Journals Publishing, 2024)
Clinical and laboratory parameters were evaluated in young patients hospitalized in an infectious disease hospital with a diagnosis of COVID-19. The study included 89 patients diagnosed with COVID-19 coronavirus infection aged 18 to 44 years, the average age was 35.8 ± 1.6 years: 59 (66.3%) men and 30 (33.7%) women. The clinical picture of the disease in most patients was characterized by the presence of bilateral viral pneumonia in 97% of cases. Concomitant diseases occurred in 32 patients (36%), most often in the group from 35 to 40 years old, while the proportion of cardiovascular diseases and obesity was 51%. Mild severity was registered in 3 (3.4%) patients, the average in 86 (96.6%) patients. In men, compared with women, symptoms of intoxication (50.6% vs. 28.2%) and shortness of breath (28.2% vs. 10.1%), dry cough, dysgeusia and loss of appetite were more common. 73% of patients had varying degrees of respiratory failure (DN), a quarter (26%) had no signs of DN. Keywords: coronavirus, COVID-19, SARS-CoV-2, young people, pneumonia, respiratory failure, computed tomography.
Keywords: coronavirus, COVID-19, SARS-CoV-2, young people, pneumonia, respiratory failure, computed tomography.